THREE NEW SPECIES OF PHAEORAMVLARIA FROM UTI AR PRADESH - C. GUPTA, KAMAL, B. K. GUPTA AND (Indian Phytopathology, 2002)
This paper deals with Phaeoramularia adenostemae sp. nov., P. buteae sp. novo and P. uttarkasiensis sp. novo causing leaf spot diseases on Adenostema sp., Butea frondosa Koen. ex Roxb. and Pogostemon plectranthoides Desf. respectively.